Do Preparation for Bias and Cultural Socialization Protect Against Discrimination for Transracially Adopted Adolescents?. Issue 2 (3rd April 2019) - Hrapczynski, Katie M.; Leslie, Leigh A.
Abstract: This study of transracially adopted adolescents and their White parents examines the role of two types of parental racial socialization, preparation for bias and cultural socialization, in protecting adoptees from the impact of discrimination. Sixty-six transracially adopted adolescent–parent dyads in the United States completed an online questionnaire. Preparation for bias, and not cultural socialization, protected transracial adoptees from discrimination-related stress, in particular when experiencing high levels of racism. The importance of parents talking to their transracially adopted adolescents about racism and how to cope with it and the value of researchers examining types of racial socialization separately as opposed to broadly are discussed.